Osmunda regalis L. in the Sierra de Madrid (Spain) - Moreno, José Manuel; Fernández González, Federico (Lazaroa, 2014)
A new record of Osmunda regalis L. in the poleozoic mountains from Madrid is reported. The locality of the record is commented as well as the chorological distribution of the taxon in the Iberian Peninsula.